Mechanism of 30S subunit recognition and modification by the conserved bacterial ribosomal RNA methyltransferase RsmI - Mohamed I. Barmada; Erin N. McGinity; Suparno Nandi; Debayan Dey; Natalia Zelinskaya; George M. Harris; Lindsay R. Comstock; Christine M. Dunham; Graeme L. Conn (Proceedings of the National Academy of Sciences, 2026)
Ribosomal RNA (rRNA) modifications are important for ribosome function and can influence bacterial susceptibility to ribosome-targeting antibiotics. The universally conserved 16S rRNA nucleotide C1402, for example, is the only 2’- O -methylated nucleotide in the bacterial small (30S) ribosomal subunit and this modification fine-tunes the shape and structure of the peptidyl tRNA binding site. The Cm1402 modification is incorporated by the conserved bacterial 16S rRNA methyltransferase RsmI, but it is unclear how RsmI recognizes its 30S substrate and specifically modify its buried target nucleotide. We determined a 2.42 Å resolution cryo-EM structure of the RsmI–30S complex and, with accompanying functional analyses, show that RsmI anchors itself to the 30S subunit through multiple contacts with a conserved 16S rRNA surface previously only seen in the assembled subunit. This positions RsmI to bind a h44 conformation that is substantially reorganized compared to its structure in the mature 30S subunit allowing access to C1402. These analyses also reveal an essential contribution to 30S subunit interaction made by the previously structurally uncharacterized RsmI C-terminal domain, RsmI-induced RNA–RNA interactions with C1402, and an unappreciated dependence on a divalent metal ion for activity that suggests RsmI may be a member of a distinct class of metal- and SAM-dependent RNA O -methyltransferases. This study significantly expands our mechanistic understanding of how intrinsic bacterial methyltransferases like RsmI modify their rRNA targets. Further, recognition of distant ribosome features and reorganization of a critical rRNA functional center point to a potential role in accurate 30S subunit biogenesis.